In Situ Synthesis and Characterization of ZnO/Chitosan Nanocomposite as an Adsorbent for Removal of Congo Red from Aqueous Solution - Nguyen, Nhu Thanh; Nguyen, Van Anh; Nguyen, Ngoc Thinh (Advances in polymer technology, 2020)
ZnO/chitosan nanocomposite was successfully synthesized by in-situ precipitation method. The material was characterized by XRD, FESEM, TEM, FTIR, BET, and TGA. Results show that ZnO/chitosan nanocomposite has spherical shape with the average size of 20–25 nm. BET surface area and the average pore size of ZnO/chitosan nanocomposite are 2.2436 (m2/g) and 12.2 nm, respectively. The material was applied as an adsorbent for congo red removal from aqueous solutions. The congo red adsorption is better described by the Langmuir model (R2=0.996) than by the Freundlich model (R2=0.962). Therefore, it can be presumed that congo red was adsorbed in a single monolayer with the theoretical maximum adsorption capacity of 227.3 (mg/g). This is comparable to other available adsorbents. It can be suggested that ZnO/chitosan nanocomposite could serve as promising adsorbent for congo red in wastewater treatment technology.